The Tumor Microenvironment and Immunotherapy of Oropharyngeal Squamous Cell Carcinoma - Welters, Marij J. P.; Santegoets, Saskia J.; van der Burg, Sjoerd H. (Frontiers in Oncology, 2020)
Oropharyngeal squamous cell carcinoma (OPSCC) develops as a consequence of several mutations in the tumor suppressor pathways or after a progressive infection with high risk human papillomavirus (HPV). The dismal side effects of the current standard of care and the clear involvement of the immune system has led to a surge in clinical trials that aim to reinforce the tumor-specific immune response as a new treatment option. In this review we have focused on the most recent literature to discuss the new findings and insights on the role of different immune cells in the context of OPSCC and its etiology. We then applied this knowledge to describe potential biomarkers and analyzed the rationale and outcomes of earlier and ongoing immunotherapy trials. Finally, we describe new developments that are still at the preclinical phase and provide an outlook on what the near future may bring, now that several new and exciting techniques to study the immune system at the single cell level are being exploited.